Primary Breast Sarcoma (Bangladesh Journal of Medical Science, 2020)
Breast sarcomas are an extremely rare and heterogeneous group of malignancies derived fromnon-epithelial elements of the gland constituting less than 1% of total breast malignanciesand less than 5% of all soft tissue sarcomas. It can be divided into two categories: de novodevelopment (primary) or secondary. These tumors are important as they have a high rate ofrecurrence and poor prognosis. In addition it is important to differentiate these tumors frombreast carcinoma as the treatment differs in these two entities. We present a case of primarybreast sarcoma in a 46 year old nulliparous Chinese woman.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.579-581